Theoretical research of selective splitting of closo-dicarba-dodecaboranes(12) under action of ammonia - S. P. Knyazev; E. G. Gordeyev; E. A. Chernyshev (Тонкие химические технологии, 2007)
Reaction of splitting of carboranes (12) under action of ammonia were investigated by the B3PW91/6-31G(d,p) method. Separate stages of process are found and quantitatively characterized. Thermodynamic and kinetic parameters of reactions were calculated